POLIGAMI DAN KEADILAN DALAM PERSPEKTIF HUKUM POSITIF: TINJAUAN LITERATUR TERHADAP PRAKTIK DI SUKU SASAK LOMBOK NTB - Kabir, Fauzul (USRAH: Jurnal Hukum Keluarga Islam, 2025)
This study discusses the practice of polygamy and justice as its main requirement, as well as how positive law in Indonesia perceives polygamy through the lens of legal validity theory. Polygamy is a complex issue as it touches upon religious, social, and legal aspects, and often sparks controversy in modern society. In Islam, polygamy is permitted under strict conditions such as justice and financial capability, which are accommodated in Law Number 1 of 1974 and the Compilation of Islamic Law. This research employs a qualitative-descriptive method based on literature study to examine the legal validity of polygamy from both normative and sociological perspectives. The findings reveal that polygamy regulations in Indonesia are legally valid; however, their enforcement is highly influenced by public acceptance and practical effectiveness. Therefore, regulations on polygamy must be continuously evaluated to remain relevant and responsive to social developments, while also upholding the values of justice within family life.